Kilconnell Franciscan Friary, north chancel wall, tomb niche, pinnacle, base - O'Donovan, Danielle (My University, 2009)
Tomb niche, base of pinnacle. Moulding, from top down comprises: necking roll, bell, bell, plinth.
Keywords: Architecture, Gothic -- Ireland; Galway (Ireland)--Buildings, structures, etc.; Architecture, Franciscan; Funerary monuments; Late Medieval; roll moldings; plinth